Regulation of properties of ebonite compositions and vulcanized anticorrosive coatings using a ftorlon filler - Saitarly, Svetlana; Plavan, Viktoriia; Pushkarev, Yuriy; Manoilenko, Oleksandr; Dmytrenko, Inna (Eastern-European Journal of Enterprise Technologies, 2017)
Ebonite compositions, which are oligo-butadienes-based, are widely used for gumming the chemical equipment and instruments that are operated in aggressive media. For the ebonite compositions with anti-corrosion purposes, of scientific and practical interest was to explore the possibility of using as a filler of chemically resistant polymeric materials, which include the ftorlon powder F-2M. We examined the effect of a ftorlon filler on the rheological properties of ebonite compositions based on 1.2-oligo-butadiene. Results of the study revealed that the compositions on the base of oligo-butadiene, filled with a ftorlon powder, are the weakly structured systems with a pseudo plastic nature of the flow. Fluctuation grids of the compositions filled with ftorlon are easily destroyed under the action of uniform shear and temperature. In order to resolve this issue and to ensure the developed coagulation structure, the compositions need to be introduced with structure-forming additives, in particular aerosil (up to 5 % by weight). We determined the dependence of strength of a vulcanizate on the sulfur content and the duration of vulcanization of coatings, which is important in order to regulate the properties and technological process of obtaining the chemically resistant coatings with improved properties. As a result of vulcanization of the examined compositions, it is possible to receive coatings with high strength (up to 27 MPa at tearing) and adhesion (9.8–10.2 MPa at tearing) without the use of specialized primers and adhesives. We explored the ohmic-capacitive characteristics and demonstrated chemical resistance of the vulcanized coatings in the 20 % solutions of sulfuric and hydrochloric acids.